Determinant of Cocoa Farming Production in Subah and Pecalungan, Batang - Lestari, Puji; Kardoyo, Kardoyo; Sudarma, Ketut (Journal of Economic Education, 2021)
The aim of this study is to analyze the influence of fund, land area, farming experience, and number of labor on a cocoa production which is moderated by a farming motivation in Subah and Pecalungan, Batang. It is a quantitative descriptive research study. A random sampling technique was used in the sample selection of simple random sampling. The data collection method was using questionnaires. The data were analyzed by a path analysis with moderated regression analysis. Results of the study shows that fund influenced the cocoa production which is moderated by the farming motivation for 0.4976 or 49.76%, land area influenced the cocoa production which is moderated by the farming motivation for 0.4853 or 48.53%, farming experience did not influence on the cocoa production which is moderated by the farming motivation for -0.0151 or -1.51%, and number of labor influenced the cocoa production which is moderated by the farming motivation for 0.5177 or 51.77%. Suggestion for the next researcher is to analyze on another variables that influence the cocoa production, for instance; amount of the productive cocoa trees, weather, and farming technology